PARADIGMA BARU DALAM PENDIDIKAN ANAK USIA DINI - Sutrisni Handayani, Ni Nyoman (PRATAMA WIDYA : JURNAL PENDIDIKAN ANAK USIA DINI, 2017)
The learning model that has been putting the burdens and shackles of children’s freedom in exploring and acquiring knowledge has now turned into how the learning process can be fun, valuable, and without unawareness. When did the educational situation arise? The situation of education takes place starting from the usual association. So, essentially social situations is a field (land) to prepare and install the education. It is because from a social situation that can be transformed into the educational or educational situation is not possible without the situation of association.